Konseling Lintas Budaya Berbasis Sumber Daya Lokal dan Kebencanaan - Hadiwinarto Hadiwinarto (Program Studi Bimbingan dan Konseling, Universitas Pattimura, 2018)
Target of this research is identify human being resources of local, psychological social needs of society, social institutes of potential local social for cross cultural konseling. Research responder 60 one who are is chosen. Data collecting by using technique of Focus Group Discussion and of cuesioner. Technique analyse data use descriptive qualitative and quantitative modestly. Result of elite indicate that disaster victim require psychological social service, ready to become volunteer cross cultural konseling and require special institute